Growth and flowering of chrysanthemum morifolium plants:ii. effect of n-mineral/n-biofertilizer and micronutrients on chrysanthemum morifolium icecap - Abdou, M. A. H. (2003)
A pot experiment was conducted during 2001 and 2002 seasons to explore the response of Chrysanthemum morifolium plants to N-mineraland/ or bio-fertilizer treatments, as well as, Fe and Zn concentrations. Both ammonium sulphate (9.6 g/pot or ammonium sulphate 4.8 glpot + nitrobein) effectively increased different vegetative growth characters, promoted flowering parameters and stimulated various chemical constituents such as N, Fe and Zn % and carbohydrates and chlorophylls contents in the leaves. Similarly, Fe or Zn gave rise to most pre-mentioned vegetative growth, flowering and chemical constituents. In general, the combined treatment consisting of Yz dose ammonium sulphate (4.8 g/pot) + nitrobein plus Fe at 80 ppm or Zn at 50 ppm gave reasonable vegetative growth and best quality and quantity of flower production.
Includes reference.
Summary in Arabic.
1
Keywords: Chrysanthemum morifolium -- Effect of minerals on